Comparative Embryonic Spatio-Temporal Expression Profile Map of the Xenopus P2X Receptor Family - Blanchard, Camille; Boué-Grabot, Eric; Massé, Karine (Frontiers in Cellular Neuroscience, 2019)
Abstract P2X receptors are ATP-gated cations channels formed by the homo or hetero-trimeric association from the seven cloned subunits (P2X1-7). P2X receptors are widely distributed in different organs and cell types throughout the body including the nervous system and are involved in a large variety of physiological but also pathological processes in adult mammals. However, their expression and function during embryogenesis remain poorly understood. Here, we report the cloning and the comparative expression map establishment of the entire P2X subunit family in the clawed frog Xenopus. Orthologous sequences for 6 mammalian P2X subunits were identified in both X. laevis and X. tropicalis, but not for P2X3 subunit, suggesting a potential loss of this subunit in the Pipidae family. Three of these genes (p2rx1, p2rx2 and p2rx5) exist as homeologs in the pseudoallotetraploid X. laevis, making a total of 9 subunits in this species. Phylogenetic analyses demonstrate the high level of conservation of these receptors between amphibian and other vertebrate species. RT-PCR revealed that all subunits are expressed during the development although zygotic p2rx6 and p2rx7 transcripts are mainly detected at late organogenesis stages. Whole mount in situ hybridization shows that each subunit displays a specific spatio-temporal expression profile and that these subunits can therefore be grouped into two groups, based on their expression or not in the developing nervous system. Overlapping expression in the central and peripheral nervous system and in the sensory organs suggests potential heteromerization and/or redundant functions of P2X subunits in Xenopus embryos. The developmental expression of the p2rx subunit family during early phases of embryogenesis indicates that these subunits may have distinct roles during vertebrate development, especially embryonic neurogenesis.